Entrepreneur Approach: Implementation of Telemedicine System for Early Detection of Stunting in Wonoayu Village, Sidoarjo - Maghfiroh, Anita Miftahul; Endro Yulianto; Syaifudin (Forum Ilmiah Teknologi dan Ilmu Kesehatan (FORITIKES), 2025)
Stunting is a serious health problem in Indonesia, especially in rural areas with limited access to health services. Wonoayu Village, Sidoarjo, is one of the areas that still faces challenges in early detection of stunting in children under five. To overcome this problem, the Partner Village Development Program (PPDM) was implemented with the aim of utilizing telemedicine technology through the Pelita application. This application is designed to help Posyandu cadres detect the risk of stunting quickly and accurately, as well as provide more effective health monitoring services. The main contributions of this program include developing the Pelita application, outreach to the community and health workers, providing tablet assistance to support application operations, as well as implementing the application in Posyandu activities. The results of this program show an increase in the capacity of Posyandu cadres in monitoring children's health, easy access to accurate health data, and faster and more efficient early detection of stunting. In conclusion, the implementation of the telemedicine system through the Pelita application has had a positive impact in overcoming the stunting problem in Wonoayu Village. This application facilitates structured monitoring of children's health, enabling early intervention for children at risk of stunting. The implication of this program is the need for continuous maintenance and development so that the application can continue to be used optimally and become a model for other regions in efforts to reduce stunting rates in Indonesia.